Understanding pragmatic markers: a variational pragmatic approach. - Aijmer, Karin (Edinburgh University Press, 2013)
The multifunctionality of pragmatic markers makes it difficult to describe their meaning and functional potential. By taking a broad perspective on markers, classifying them, describing their class-specific properties and analysing individual markers, Karin Aijmer assesses whether generalisations can be made about the prosody of the markers.